The hero legend in colonial Southeast Asia - Gibson, Thomas (Philippine studies : historical and ethnographic viewpoints, 2013)
"Four legends that originated in the different religious and colonial contexts of the Tagalog and Makassar peoples are shown to conform to Edward Tylor's classical "hero pattern." Using structural anthropology and cognitive linguistics, this article argues that hero legends generated metaphors from concrete relationships in the domestic domain to conceptualize abstract relationships in a series of other domains. The hero pattern underwent transformations in tandem with changes in the political and economic institutions in which it was embedded. From its beginnings as a charter for rival city-states in the ancient Middle East, it became a charter for the universalistic world religions that arose within the empires that succeeded the city-states. In the Souteast Asian legends discussed here, it served as a charter for both collaboration with and resistance to colonial rule."